2022
DOI: 10.1002/nano.202200027
|View full text |Cite
|
Sign up to set email alerts
|

Multi‐parametric surface plasmon resonance‐based intake quantification of label‐free light‐activated nanoparticles by therapeutic limbal stem cells for corneal blindness

Abstract: Advanced therapies with combined approaches of cell and nanomedicine‐based interventions are emerging. Corneal blindness with a severe form of limbal stem cell (LSC) deficiency is an example of defect with unmet clinical need. Towards cell‐based therapy, advanced enabling technologies are needed for efficient intracellular delivery of biomolecules both for in vitro disease modeling and for in vivo interventions. For this nanomedicine creates novel possibilities as light activatable polymeric nanoparticles (NPs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 36 publications
0
1
0
Order By: Relevance
“…Based on the flow cytometry results, it is apparent that the SPR responses and kinetics measured in this study during interaction of chitosomes with cell monolayers merely reflect the strength and ability of the chitosomes to interact with the cell surface, not the cell uptake efficacy, even though in earlier studies the SPR PAP responses have been shown to reflect also the cell uptake efficacy of other types of nanoparticles. 9 , 41 43 Nonetheless, SPR measurements have their value in providing insights on the real-time interactions of nanoparticles with cells, especially as the measurements can be performed without the use of any labels that can affect the physicochemical properties of the nanoparticles of interest or affect cell behavior. Although it might be difficult to pinpoint the actual origin for the SPR PAP responses when measuring nanoparticle interactions with cells, i.e., cell surface interaction or cell uptake of nanoparticles, the SPR PAP responses and the rate constants extracted from the results can nevertheless be related to the strength of interaction or ability of the nanoparticles to interact with cells, which consequently reflects the drug delivery efficacy or targetability of the nanoparticles of interest.…”
Section: Resultsmentioning
confidence: 99%
“…Based on the flow cytometry results, it is apparent that the SPR responses and kinetics measured in this study during interaction of chitosomes with cell monolayers merely reflect the strength and ability of the chitosomes to interact with the cell surface, not the cell uptake efficacy, even though in earlier studies the SPR PAP responses have been shown to reflect also the cell uptake efficacy of other types of nanoparticles. 9 , 41 43 Nonetheless, SPR measurements have their value in providing insights on the real-time interactions of nanoparticles with cells, especially as the measurements can be performed without the use of any labels that can affect the physicochemical properties of the nanoparticles of interest or affect cell behavior. Although it might be difficult to pinpoint the actual origin for the SPR PAP responses when measuring nanoparticle interactions with cells, i.e., cell surface interaction or cell uptake of nanoparticles, the SPR PAP responses and the rate constants extracted from the results can nevertheless be related to the strength of interaction or ability of the nanoparticles to interact with cells, which consequently reflects the drug delivery efficacy or targetability of the nanoparticles of interest.…”
Section: Resultsmentioning
confidence: 99%